NK1.1+ innate lymphoid cells in salivary glands inhibit establishment of tissue‐resident memory CD8+ T cells in mice. Issue 12 (17th August 2020) - Woyciechowski, Sandra; Weißert, Kristoffer; Ammann, Sandra; Aichele, Peter; Pircher, Hanspeter
Abstract: NK1.1 + cells found in salivary glands (SG) represent a unique cell population of innate lymphoid cells (ILC) with characteristics of both conventional NK cells and ILC1. Here, we demonstrate that these NK1.1 + cells limit the accumulation and differentiation of virus‐specific tissue‐resident memory CD8 + T cells (TRM cells) in SG of mice infected with lymphocytic choriomeningitis virus (LCMV). The negative regulation of LCMV‐specific CD8 + TRM cells by NK1.1 + cells in SG is independent of NKG2D, NKp46, TRAIL, and perforin. Moreover, analysis of NKp46 iCre+ Eomes fl/fl mice revealed that Eomes‐dependent conventional NK cells are dispensable for negative regulation. Since the SG are prone to autoimmune reactions, regulation of TRM cells by tissue‐resident ILC may be particularly important to prevent immunopathology in this organ. Abstract : The salivary glands harbor a unique subset of NK1.1 + ILC with characteristics of both conventional NK cells and ILC1. Here, we demonstrate that these cells limit the accumulation and differentiation of tissue‐resident memory T cells (TRM cells) in mice after viral infection. In addition, we show that NKp46, NKG2D, TRAIL, perforin, and Eomes‐dependent conventional NK cells were dispensable for this type of negative regulation.